Evaluation of Agricultural Production Data of TRB1 Region for Adaptation to Climate Change - Çelik, Kürşat (Fırat University, 2023)
Although climate change has been a natural phenomenon throughout human history, it has become a more serious problem today. The effects of climate change directly affect human life and the development of civilizations. Therefore, combating and adapting to climate change is the responsibility of both states and individuals. Ancient communities in Anatolia and its surroundings that lived in the past took various precautions and developed innovations against climate change. These measures and innovations can still set an example and inspire us today. To minimize the effects of climate change, risk management and measures to be taken at critical control points are vital. The aim of this study is to determine the agricultural products grown from past to present in the TRB1 region (Bingöl, Elazığ, Malatya and Tunceli) and thus contribute to the adaptation and adaptation processes to climate change. In this study, the amounts of basic products produced in the fields of crop production and livestock farming in the TRB1 region were compared according to the population of the provinces and their trends of increase or decrease were examined. Thus, the change in cultivation areas and product patterns in the TRB1 region between past and present was revealed. Today, it has been determined that the most grown products in the TRB1 region are grains. It is noteworthy that among these products, barley replaced wheat. Due to natural disasters that occur every year in the region due to climate change, large fluctuations in product quantities have occurred. The most sensitive sector in the region is beekeeping and honey production. Over time, cattle farming replaced small livestock farming in the region.

İklim değişikliği, insanlık tarihi boyunca karşılaşılan doğal bir olay olmakla birlikte, günümüzde daha ciddi bir sorun haline gelmiştir. İklim değişikliğinin etkileri, insan hayatını ve uygarlıkların gelişimini doğrudan etkilemektedir. Bu nedenle, iklim değişikliğiyle mücadele etmek ve uyum sağlamak, hem devletlerin hem de bireylerin sorumluluğudur. Geçmişte yaşamış olan Anadolu ve çevresindeki eski topluluklar, iklim değişikliğine karşı çeşitli önlemler almış ve yenilikler geliştirmişlerdir. Bu önlemler ve yenilikler, günümüzde de bize örnek olabilir ve ilham verebilir. İklim değişikliğinin etkilerini en aza indirmek için, risk yönetimi ve kritik kontrol noktalarında alınması gereken önlemler hayati önem taşımaktadır. Bu çalışmanın amacı, TRB1 bölgesinde (Bingöl, Elazığ, Malatya ve Tunceli) geçmişten günümüze yetiştirilen tarımsal ürünlerin belirlenmesi ve böylece iklim değişikliğine uyum ve adaptasyon süreçlerine katkıda bulunmaktır. Bu çalışmada, TRB1 bölgesinde bitkisel üretim ve hayvancılık alanlarında üretilen temel ürünlerin miktarları illerin nüfusuna göre karşılaştırılmış ve artış veya azalış eğilimleri incelenmiştir. Böylelikle, TRB1 bölgesindeki ekim alanları ve ürün desenlerinin geçmişle günümüz arasındaki değişimi ortaya konmuştur. Günümüzde, TRB1 bölgesinde en fazla yetiştirilen ürünlerin hububat olduğu tespit edilmiştir. Bu ürünler arasında, buğdayın yerini arpanın aldığı dikkat çekmektedir. Bölgede iklim değişikliğine bağlı olarak her yıl yaşanan doğal afetler nedeniyle ürün miktarlarında büyük dalgalanmalar meydana gelmiştir. Bölgedeki en hassas sektör arıcılık ve bal üretimidir. Bölgede küçükbaş hayvancılığın yerini zamanla büyükbaş hayvancılık almıştır.
İKLİM DEĞİŞİKLİĞİNE ADAPTASYON İÇİN TRB1 BÖLGESİNİN TARIMSAL ÜRETİM VERİLERİNİN DEĞERLENDİRİLMESİ
Keywords: Ecological Economics; Ekolojik İktisat; Regional Economy; Bölgesel Ekonomi